Transforming Decommissioned Mines to a Gravity Energy Storage System - Michail Galetakis; Georgios Biotakis; Vasilios Deligiorgis; Emmanouil Varouchakis (Materials Proceedings, 2023)
A new gravitational energy storage system is studied, which uses a reversible conveyor belt to elevate granular material and a regenerative motor for energy harvesting during the downward movement of material. This system can be installed in decommissioned open-pit mines, which offer suitable topography and available material. The parameters affecting the performance of this energy storage system are examined by employing sensitivity/uncertainty analysis. Results showed that the inclination of the conveyor, the filling factor of the conveyor belt, and the efficiency of the motor/generator had the greatest impact on the overall energy storage efficiency.